The planetary system: Web 3.0 & active documents for STEM - Kohlhase, Michael; Corneli, Joe; David, Catalin; Ginev, Deyan; Jucovschi, Constantin; Kohlhase, Andrea; Lange-Bever, Christoph; Matican, Bogdan; Zholudev, Vyacheslav; et al. (11th International Conference on Computational Science, ICCS 2011, 2011)
In this paper we present the Active Documents Paradigm (semantically annotated documents associated with a content commons that holds the corresponding background ontologies) and the Planetary system (as an active document player). We show that the current Planetary system gives a solid foundation and can be extended modularly to address most of the criteria of the Executable Papers Challenge.
Keywords: Active documents; Content commons; Executable paper challenge; Ontologies; Semantic annotation